Money-prices causation in foru CARICOM economies : a preliminary investigation - Nicholls, S. M. A. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Investigates the direction of causality between money and prices in Barbados, Guyana, Jamaica and Trinidad and Tobago.